2021
DOI: 10.1155/2021/8223216
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the 7-lncRNA Signature as a Prognostic Biomarker for Acute Myeloid Leukemia

Abstract: A lot of evidence has emphasized the function of long noncoding RNAs (lncRNAs) in tumors’ development and progression. Nevertheless, there is still a lack of lncRNA biomarkers that can predict the prognosis of acute myeloid leukemia (AML). Our goal was to develop a lncRNA marker with prognostic value for the survival of AML. AML patients’ RNA sequencing data as well as clinical characteristics were obtained from the public TARGET database. Then, differentially expressed lncRNAs were identified in female and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, none of these lncRNA have defined functions in cancer or AML, thereby highlighting the value of lncRNAs as biomarkers independent of their mechanism (C. Y. Liu et al, 2021).…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, none of these lncRNA have defined functions in cancer or AML, thereby highlighting the value of lncRNAs as biomarkers independent of their mechanism (C. Y. Liu et al, 2021).…”
Section: Biomarkersmentioning
confidence: 99%
“…They found that their 7‐lncRNA signature (LINC00461, RP11—309 M23.1, AC016735.2, RP11—61I13.3, KIAA0087, RORB—AS1, AC012354.6) was able to accurately predict patient outcome with patients with a high “risk score” having poor OS compared to the low‐risk score cohort. Interestingly, none of these lncRNA have defined functions in cancer or AML, thereby highlighting the value of lncRNAs as biomarkers independent of their mechanism (C. Y. Liu et al, 2021 ).…”
Section: Lncrna Function In Cancer and Amlmentioning
confidence: 99%
“…Emerging evidence has identified that various ir-lncRNAs have significant associations with the cancer cell response to anti-PD-1 immunotherapy in multiple tumors [ 6 , 7 ]. Some lncRNA signatures have been identified in AML, and their expression was associated with the survival of patients with AML [ 8 10 ]. Still, all these prognostic models were established based on the expression of lncRNAs, which limited the clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Serum LINC00899 was predicted to be a potential and useful noninvasive biomarker for the early clinical detection and prognosis of AML (Wang et al, 2018). Interestingly, several lncRNA-based integrated models have been developed for the stratification of AML patients (Liu et al, 2021;Zhu et al, 2023). Recently, an integrated prognostic signature encompassing five immunerelated protein-coding genes and an immune-related lncRNA has been successfully constructed to predict the survival and stratification of AML patients (Zhao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%